Research on the Bonding Performance of BFRP Bars with Reactive Powder Concrete - Jie Xiao; Yikang Murong; Xiyuan Chen; Lingfei Liu; Keyi Zhai; Haibo Jiang; Linhai Huang; Guodong Wang (Buildings, 2023)
In recent years, replacing steel bars with basalt fiber-reinforced polymer (BFRP) bars and replacing ordinary concrete with reactive powder concrete (RPC) are considered effective solutions to the corrosion problem of steel bars in ordinary reinforced concrete structures. In order to study the bonding performance between BFRP bars and RPC, a total of 27 bonding specimens were tested by pull-out test. The effects of steel fiber volume content (0%, 1.5%, 2%), protective layer thickness (25 mm, 40 mm, 55 mm, 69 mm), and bond anchorage length of bars (3 d, 4 d, 5 d; d is the diameter of the bars) on the bond performance were studied. The experimental results indicated that the BFRP bar and reactive powder (RPC) concrete interface exhibited better bonding performance, and the steel fibers mixed in RPC can play the role of crack-blocking enhancement in the specimen, which improves the shear and tensile properties of the concrete, thus improving the bond strength between BFRP bar and RPC. Three failure modes were observed in the pull-out tests: BFRP bar shear failure, splitting failure, and concrete shear failure. The bond strengths of BFRP bars and RPC with 0%, 1.5%, and 2% steel fiber content were 24.2 MPa, 32.1 MPa, and 34.5 MPa, respectively. With the increase in bond anchorage length, the ultimate bond strength tended to increase first and then decrease. There may be an optimal bonding length between BFRP bar and reactive powder concrete, and when the optimal bonding length is exceeded, the bond strength decreases with the increase in bonding length. With the increase in the protective layer thickness, the improvement in the bond strength of the BFRP bar and RPC was not very significant.